AUTOINSTRUIREA - FUNDAMENTUL DE BAZĂ AL MODERNIZĂRII ÎNVĂŢĂMÂNTULUI SUPERIOR - USM ADMIN (Moldova State University, 2010)
The article is devoted to the investigation of self-learning skills and self-training for the students - future teachers. In this article the structure of self-learning competences, internal and external factors, that influence the learning activity and conditions for the formation of motivation are analyzed. The conclusion is that preparation of students for self-learning is of great importance in professional training system.